Excavatability and the effect of weathering degree on the excavatability of rock masses: An example from Eastern Turkey - Gurocak, Zulfu; Yalcin, Erkut (Pergamon-Elsevier Science Ltd, 2016)
In this study, the effect of the weathering degree on the excavatability of rock masses was investigated. The ophiolitic rock mass along the route of Komurhan Tunnel was chosen as the case study. Both laboratory and field studies were carried out for this purpose. In the first stage, the ophiolitic rock mass along the tunnel route was classified into three subzones according to the weathering degree and the ophiolitic rock masses of the each subzones were classified using the empirical excavatability classifications proposed by the different researchers. Furthermore, in-situ excavatability classes of rock masses in each zone were determined and the results were compared. The in-situ excavatability class of fresh (Zone-I) and slightly weathered (Zone-II) rock masses was determined as Blasting and that of moderately weathered (Zone-III) rock mass was determined as Very Hard/Very Difficult. As the obtained results were compared, it was found that the weathering degree has a significant effect on the excavatability and that it is more appropriate to prefer empirical classifications in the empirical determination of excavatability classes of rock masses having the same lithology by taking the weathering degree into account. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Degree of weathering; Excavatability; Komurhan tunnel; Rippability